Neuro-Linguistic Programming (NLP)-Based Scrapbook Media to Improve Poetry Writing Skills of Fourth Grade Elementary School Students - Yunita Sari, Ni Komang; Maria Goreti Rini Kristiantari; Basilius Raden Werang (Jurnal Media dan Teknologi Pendidikan, 2025)
The low level of poetry writing skills among elementary school students highlights the need for innovative learning media that can facilitate a more enjoyable and meaningful learning process. This study aims to develop a scrapbook-based learning media integrated with Neuro Linguistic Programming (NLP) to improve poetry writing skills of fourth-grade students. This research employs a research and development (R&D) method using the ADDIE model. Data collection techniques include observation, interviews, questionnaires, and tests, while the data were analyzed using descriptive quantitative and qualitative methods. The validation results indicate that the developed media is highly feasible, with expert ratings of 93.75% (content), 92.50% (design), and 90.62% (media). Practicality tests scored 93.75% from teachers, 94.69% from individual trials, and 93.93% from small group trials. Effectiveness testing showed an increase in the average score from 69.66 to 91, with tvalue = 15.025 > ttable = 1.761. The study concludes that the scrapbook media based on NLP is valid, practical, and effective in enhancing students’ poetry writing skills. The implication is that this media can serve as an innovative alternative in writing instruction, fostering creative expression and increasing students’ learning motivation.